Incorporating interface affected zones into crystal plasticity. (February 2015) - Mayeur, J.R.; Beyerlein, I.J.; Bronkhorst, C.A.; Mourad, H.M.
Highlights: A crystal plasticity model with interface affected zones (IAZ) is presented. Slip is biased within the IAZ towards systems favorably aligned for slip transfer. The model is used to study the orientational stability of Cu–Nb bicrystals. Simulation results show that the IAZ modifies the stability of certain interfaces. Abstract: This work presents a crystal plasticity modeling framework that accounts for the influence of material interfaces on the plastic behavior of the two crystals on either side of the interface. Within an interface-affected zone (IAZ) extending from both sides of the interface, slip system activity is presumed to be biased towards systems that permit slip transfer across the interface. The preferred slip transfer pathways are determined from the geometric alignment of the slip systems and the stress state within each crystal. The IAZ model is applied to study the plastic stability of Cu–Nb bicrystals under plane strain compression. Our results show that the additional constraints imposed through the enforcement of slip continuity across the interface leads to reduced plastic stability as compared to the case without an IAZ for several of the interfaces studied.